The impact of uncertainty in repair service attributes on consumer preferences: Insights from a dual‐response choice experiment - Bengart, Paul; Vogt, Bodo (Journal of industrial ecology, 2025)
Extending the lifespan of electronic devices through repair can significantly reduce negative environmental impacts. However, despite consumers reporting a strong preference for repair, actual repair rates remain relatively low. Qualitative research has indicated that uncertainty surrounding various aspects of repair service offers, such as repair costs and outcomes, discourages consumers from choosing repair. However, no studies have yet quantified the effects of varying degrees of uncertainty in repair service attributes on consumers' preferences for repair and repair services. This study addresses this gap using a dual‐response choice‐based conjoint analysis with 237 German consumers, manipulating the degree of uncertainty in the attributes repair success rate and total repair cost of hypothetical repair offers. Other attributes examined included repair service provider, repair time, and warranty. Results show that even vague information substantially increases preferences for repair compared to offering no information at all, nearly doubling the choice share of a repair offer. However, consumers may tolerate or even prefer some pricing uncertainty if it offers the possibility of a more favorable outcome. The study further reveals that consumers with prior repair experience tend to show higher willingness to choose repair services compared to those without such experience. Overall, the findings suggest that the lack of transparency about potential repair outcomes and costs, which is common in real‐world repair offers, acts as a major barrier discouraging many consumers from choosing repair.